2012
DOI: 10.1371/journal.pone.0036622
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide-Mediated Apparent Displacement between Two Invasive Species of Leafminer Fly

Abstract: BackgroundClosely related invasive species may often displace one another, but it is often difficult to determine mechanisms because of the historical nature of these events. The leafmining flies Liriomyza sativae and Liriomyza trifolii have become serious invasive agricultural pests throughout the world. Where both species have invaded the same region, one predominates over the other. Although L. sativae invaded Hainan Island of China first, it recently has been displaced by the newly invasive L. trifolii. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…The causes of the demographic change are not always clear and may be attributed to various biological mechanisms or anthropogenic factors, including differences in their respective reproductive success, and susceptibility to acaricides. Similar effects can be seen in other insect species, where it has been reported that the application of insecticides can lead to rapid shifts in the composition of leafminer complexes in laboratory and field‐based experiments (Gao, Reitz, Wei, Yu, & Lei, 2012). Although the greater resistance of T. urticae versus T. cinnabarinus to acaricides is generally recognized, it is unclear whether acaricides facilitate the expansion of T. urticae , resulting in T. urticae being the dominant species of spider mites.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…The causes of the demographic change are not always clear and may be attributed to various biological mechanisms or anthropogenic factors, including differences in their respective reproductive success, and susceptibility to acaricides. Similar effects can be seen in other insect species, where it has been reported that the application of insecticides can lead to rapid shifts in the composition of leafminer complexes in laboratory and field‐based experiments (Gao, Reitz, Wei, Yu, & Lei, 2012). Although the greater resistance of T. urticae versus T. cinnabarinus to acaricides is generally recognized, it is unclear whether acaricides facilitate the expansion of T. urticae , resulting in T. urticae being the dominant species of spider mites.…”
Section: Introductionsupporting
confidence: 66%
“…Similarly, Gao, Lei, Abe, and Reitz (2011), Gao et al. (2012) suggested that differential susceptibility to commonly used insecticides could account for the replacement of Liriomyza sativae by Liriomyza trifolii on Hainan Island of southern China (Gao et al., 2011, 2012). However, the underpinning mechanisms behind the differential susceptibility to insecticides for these Bemisia spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,26,28 While no unique, specific mechanisms have been identified as causing the displacement of L. sativae by L. trifolii, field surveys have indicated that insecticide use can produce significant changes in the complex of Liriomyza species in China. 29 L. trifolii populations tend to be more tolerant to commonly used insecticides than L. sativae. Studies indicate that the capacity of L. trifolii populations to develop insecticide resistance has enabled it to replace L. sativae as the primary leafminer in several cropping sytems.…”
Section: Influence Of Abiotic Factors On Species Displacementmentioning
confidence: 99%
“…While no unique, specific mechanisms have been identified as causing the displacement of L. sativae by L. trifolii , field surveys have indicated that insecticide use can produce significant changes in the complex of Liriomyza species in China . L. trifolii populations tend to be more tolerant to commonly used insecticides than L. sativae .…”
Section: Influence Of Abiotic Factors On Species Displacementmentioning
confidence: 99%